Validation of Protein Biomarkers to Advance the Management of Autoimmune Disorders - Gibson, David S.; Finnegan, Sorcha; Pennington, Stephen; Qiu, Ji; LaBaer, Joshua; Rooney, Madeleine E.; Duncan, Mark W. (IntechOpen, 2011)
None